Efek Kepuasan Kerja sebagai Variabel Moderasi pada Pengaruh Transformasi Digital dan Kepemimpinan Birokratis terhadap Kinerja Pegawai Kantor Wilayah Kementerian Agama Provinsi Sumatera Selatan - Etty Sri Wahyuni; Msy. Mikial; Ima Andriyani; Sari Sakarina (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to analyze the influence of digital transformation and bureaucratic leadership on employee performance with job satisfaction as a moderating variable at the Regional Office of the Ministry of Religious Affairs of South Sumatra Province. The study used a quantitative descriptive-correlational approach with a census method on 57 Government Employees with Work Agreements (P3K). Data were collected through a five-point Likert scale questionnaire supported by interviews and documentation. Data analysis was conducted using PLS-SEM with the help of SmartPLS version 3.2.9. The results of the analysis indicate that digital transformation and bureaucratic leadership have a positive and significant influence on employee performance. Job satisfaction is also proven to contribute significantly to improving employee performance. However, testing the moderation effect shows that job satisfaction is unable to moderate the relationship between digital transformation and bureaucratic leadership with employee performance. This indicates that employee performance is more influenced by the direct influence of each of these variables. The research findings indicate that improving employee performance in the public sector is mainly influenced by the effectiveness of digital transformation and bureaucratic leadership. Although job satisfaction plays a role in improving performance, this variable does not function as a moderator. Therefore, performance improvement efforts need to focus on strengthening technology implementation and bureaucratic leadership, along with increasing employee job satisfaction. This study was limited to a single government agency with 57 respondents, which may limit the generalizability of the results. Other potential influencing factors, such as organizational culture or external conditions, were not examined in this study. This study provides theoretical contributions regarding the relationship between digital transformation and leadership in public sector performance. Practically, this research provides guidance for policymakers and agencies in developing initiatives that integrate technology, leadership, and job satisfaction to optimize organizational outcomes.